Exploring Low-Waste Patternmaking Techniques for Sustainable Solutions in Fashion Industry - Umer Hameed; Shahid Zaheer; Nabeel Amin; Sajid Hussain (Journal of Design and Textiles, 2023)
In the realm of sustainable fashion, designers are actively exploring innovative strategies to reshape their design processes. This study aims to unveil foundational sustainability principles integrated into sustainable fashion praxis using design thinking methodologies. The focus is on practical low-waste patternmaking as a testing ground to assess these principles' feasibility. The research methodology employs a qualitative framework grounded in pragmatism, allowing for a deep engagement in an exploratory data collection process led by a researcher-practitioner in the field of fashion design. While the primary focus is on the core fashion design process, the goal is to align sustainability strategies with key stages in conventional design and production. By aligning the fundamental fashion design process with responsible consumption and production, the study advocates for the adoption of innovative methods that deviates from traditional practices. The study's findings presented comparative insights between conventional approaches and modern sustainable practices. Further exploration of digital advancements in pattern design can streamline sustainability implementation. In conclusion, this challenging yet rewarding study emphasized practical problem-solving strategies in a fashion that is distinct from technical and creative knowledge applications.